2010
DOI: 10.3233/jad-2010-100123
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Variation in Cytochrome Oxidase Subunit Genes

Abstract: Cytochrome oxidase (COX) activity varies between individuals and low activities associate with Alzheimer's disease. Whether genetic heterogeneity influences function of this multimeric enzyme is unknown. To explore this we sequenced three mitochondrial DNA (mtDNA) and ten nuclear COX subunit genes from at least 50 individuals. 20% had non-synonymous mtDNA COX gene polymorphisms, 12% had a COX4I1 non-synonymous G to A transition, and other genes rarely contained non-synonymous polymorphisms. Frequent untranslat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Indeed, defects in mtDNA associated with decreased cytochrome oxidase activity have been found in AD patients (9). Although a similarly impaired mitochondrial function and subsequent compensatory response have been observed in both nondemented aged and AD subjects, no clear causative mutations in the mtDNA have been correlated to AD; although some variations have functional consequences, including changes in enzymatic activity (40). Perhaps the main differences are that, in AD brains, defects are more profound due to Ab and tau accumulation, because of decreased compensatory response machinery (Fig.…”
Section: Mitochondrial Aging-the Beginning Of the End In Ad?mentioning
confidence: 99%
“…Indeed, defects in mtDNA associated with decreased cytochrome oxidase activity have been found in AD patients (9). Although a similarly impaired mitochondrial function and subsequent compensatory response have been observed in both nondemented aged and AD subjects, no clear causative mutations in the mtDNA have been correlated to AD; although some variations have functional consequences, including changes in enzymatic activity (40). Perhaps the main differences are that, in AD brains, defects are more profound due to Ab and tau accumulation, because of decreased compensatory response machinery (Fig.…”
Section: Mitochondrial Aging-the Beginning Of the End In Ad?mentioning
confidence: 99%
“…However, estimates of heritability may 80 be biased if non-autosomal sources of heritable variation are present but not modeled, leading to erroneous conclusions about the evolvability of a trait. Based on the shared biochemical pathways of intracellular energy production and the oxidation of carotenoids, Johnson and Hill (2013) recently suggested that carotenoid metabolism takes place at the inner mitochondrial membrane, highlighting the potential for functional sequence variation in the mitochondrial 85 genome (Lu et al 2010) to impact directly on coloration, much as it impacts aerobic performance (Harrison and Turrion-Gomez 2006;Niemi and Majamaa 2005). Given that mitochondria are maternally inherited (Brown 2008; though paternal leakage of mitochondrial DNA has been reported in birds: Kvist et al 2003), this raises the possibility that variation in carotenoid-based coloration is associated with extranuclear genetic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreira (130) and de la Monte (46) reported that AD brains present increased fragmentation of mtDNA, reduced mtDNA content and mass, reduced level of COX, and evidence of apoptotic cell loss. Despite no causative mtDNA mutations being linked to AD, some polymorphic variations can occur, having implications in enzymatic activities, such as COX (109). Some mtDNA mutations have been associated with increased incidence of AD (195,43).…”
Section: Alzheimer's Diseasementioning
confidence: 99%